Woman, native, other: Writing postcoloniality and feminism - Trinh, T. Minh-Ha (Indiana University Press., 1989)
"" ... Methodologically innovative ... precise and perceptive and conscious ... ""--Text and Performance Quarterly""Woman, Native, Other is located at the juncture of a number of different fields and disciplines, and it genuinely succeeds in pushing the boundaries of these disciplines further. It is one of the very few theoretical attempts to grapple with the writings of women of color.""--Chandra Talpade Mohanty""The idea of Trinh T. Minh-ha is as powerful as her films ... formidable ... ""--Village Voice"" ... its very forms invite the reader to participate in the effort to understand how language
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; fem1000; fem3200; féminisme décolonial; littérature; premier cycle; périodes historiques; ressource en ligne; thématiques; écriture des femmes*; études littéraires

Woman, native, other: writing postcoloniality and feminism - Trinh, T. Minh-Ha (Indiana University Press, 1989)
" . . . methodologically innovative . . . precise and perceptive and conscious . . . " —Text and Performance Quarterly "Woman, Native, Other is located at the juncture of a number of different fields and disciplines, and it genuinely succeeds in pushing the boundaries of these disciplines further. It is one of the very few theoretical attempts to grapple with the writings of women of color." —Chandra Talpade Mohanty "The idea of Trinh T. Minh-ha is as powerful as her films . . . formidable . . . " —Village Voice " . . . its very forms invite the reader to participate in the effort to understand how language structures lived possibilities." —Artpaper "Highly recommended for anyone struggling to understand voices and experiences of those 'we' label 'other'." —Religious Studies Review Audio book narrated by Betty Miller. Produced by Speechki in 2021.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; premier cycle; périodes historiques; ressource en ligne; thématiques; écriture des femmes*; études littéraires

Borderlands: The new mestiza - Anzaldúa, Gloria (Spinsters, Aunt Lute, 1987)
Rooted in Gloria Anzaldúa’s experience as a Chicana, a lesbian, an activist, and a writer, the groundbreaking essays and poems in this volume profoundly challenged how we think about identity. Borderlands/La Frontera remapped our understanding of what a “border” is, seeing it not as a simple divide between here and there, us and them, but as a psychic, social, and cultural terrain that we inhabit, and that inhabits all of us. This twentieth-anniversary edition features new commentaries from prominent activists, artists, and teachers on the legacy of Gloria Anzaldúa’s visionary work
Keywords: amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; féminisme décolonial; identités LGBTQIA2+; lit3220; littérature; mexique; pol4212; premier cycle; queer; régions géographiques; thématiques; états-unis; études littéraires

Feminism and nationalism in the Third World - Jayawardena, Kumari (Zed Books, 1986)
Un texte fondateur du féminisme transnational Depuis vingt-cinq ans, Feminism and Nationalism in the Third World est une introduction essentielle à l'histoire des mouvements de femmes en Asie et au Moyen-Orient à la fin du XIXe et au début du XXe siècle. Dans cette enquête engageante et bien documentée, Kumari Jayawardena présente le féminisme tel qu'il est né dans le Tiers-Monde, émergeant des luttes spécifiques des femmes luttant contre le pouvoir colonial, pour l'éducation ou le vote, pour la sécurité, et contre la pauvreté et les inégalités.
Keywords: 1800-1899; 1900-1999; afrique; approches et analyses; asie; cours; fem1000; féminisme décolonial; féminisme transnational; inégalités; nationalisme; premier cycle; périodes historiques; régions géographiques; sud global; systèmes d'oppressions; théories féministes

L'orientalisme : l'Orient créé par l'Occident - Said, Edward W. (Seuil, 1980)
D'Eschyle à Kissinger, de Marx à Barrès, l'Occident a tenu un discours sur l'Orient. Mais, puisque «l'Orient» n'existe pas, d'où vient ce discours et comment expliquer son étonnante stabilité à travers les âges et les idéologies? «L'Orient» est une création de l'Occident, son double, son contraire, l'incarnation de ses craintes et de son sentiment de supériorité tout à la fois, la chair d'un corps dont il ne voudrait être que l'esprit. À étudier l'orientalisme, présent en politique et en littérature, dans les récits de voyage et dans la science, on apprend donc peu de choses sur l'Orient, et beaucoup sur l'Occident. Le portrait que nous prétendons faire de l'Autre est, en réalité, tantôt une caricature, tantôt un complément de notre propre image. L'idéologie orientaliste s'est échappée depuis longtemps déjà du cabinet des savants pour précéder Napoléon dans sa conquête de l'Égypte ou suivre la guerre du Liban. C'est de ce discours qu'on trouvera ici la magistrale archéologie, augmentée de la préface que l'auteur rédigea en 2003 pour le vingt-cinquième anniversaire de la publication originale de l'ouvrage.
Keywords: amériques; approches et analyses; arts; com5170; cours; discipline; discours dominant; europe; fem1000; fem3400; féminisme décolonial; har4600; har4610; occident; orient; premier cycle; régions géographiques; systèmes d'oppressions; thématiques; violences; études littéraires